2021
DOI: 10.1007/s40097-021-00404-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel UV-activated biofunctionalization of up-converting nanocrystals for detection of proteins

Abstract: Lanthanide doped nanocrystals capable to emit higher energy photons under excitation with lower energy radiation are promising for a broad range of applications including biodetection, biosensing, and bioimaging. However, the adaptation of these nanoparticles to the biological environment that requires good water-solubility, stability and ease of further functionalization still remains a challenge. The application of nanoparticles for biodetection or in various assays encountered many difficulties arising main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, Misiak et al reported on the use of UCNP labels in dot-blot immunoassays, however, focusing on different analytes. In their work, UCNPs were successively coated with a polyvinylpyrrolidone/vinyl alcohol copolymer, aminated dextran, and protein G. The prepared labels were then employed in semiquantitative detection of various targets, in particular, lipopolysaccharide from Escherichia coli (LOD of 1.95 μg/mL), murine monoclonal antibodies (LOD of 0.19 μg/mL), and immunoglobulin from human serum (LOD of 0.49 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Misiak et al reported on the use of UCNP labels in dot-blot immunoassays, however, focusing on different analytes. In their work, UCNPs were successively coated with a polyvinylpyrrolidone/vinyl alcohol copolymer, aminated dextran, and protein G. The prepared labels were then employed in semiquantitative detection of various targets, in particular, lipopolysaccharide from Escherichia coli (LOD of 1.95 μg/mL), murine monoclonal antibodies (LOD of 0.19 μg/mL), and immunoglobulin from human serum (LOD of 0.49 μg/mL).…”
Section: Resultsmentioning
confidence: 99%
“… 36 However, only one study has used UCNPs as labels for the sensitive quantitation of analyte concentrations in dot-blot. Misiak et al 37 used dextran-coated UCNPs conjugated with protein G for the detection of various protein targets, such as murine monoclonal antibodies, obtaining the LOD of 0.19 μg/mL. However, this study was not able to achieve sub-ng/mL detection limits, which are necessary for the sensitive detection of many low-abundance clinical biomarkers (defined by Kim et al 38 as biomarkers with concentrations below 10 ng/mL).…”
Section: Introductionmentioning
confidence: 86%